Ecohydrological responses to surface flow across borders: Two decades of changes in vegetation greenness and water use in the riparian corridor of the Colorado River delta. Issue 25 (9th October 2020) - Nagler, Pamela L.; Barreto‐Muñoz, Armando; Chavoshi Borujeni, Sattar; Jarchow, Christopher J.; Gómez‐Sapiens, Martha M.; Nouri, Hamideh; Herrmann, Stefanie M.; Didan, Kamel
Abstract: Hydrological and bioclimatic processes that lead to drought may stress plants and wildlife, restructure plant community type and architecture, increase monotypic stands and bare soils, facilitate the invasion of non‐native plant species and accelerate soil erosion. Our study focuses on the impact of a paucity of Colorado River surface flows from the United States (U.S.) to Mexico. We measured change in riparian plant greenness and water use over the past two decades using remotely sensed measurements of vegetation index (VI), evapotranspiration (ET) and a new annualized phenology assessment metric (PAM) for ET. We measure these long‐term (2000–2019) metrics and their short‐term (2014–2019) response to an environmental pulse flow in 2014, as prescribed under Minute 319 of the 1944 Water Treaty between the two nations. In subsequent years, small‐directed flows were provided to restoration areas under Minute 323. We use 250 m MODIS and 30 m Landsat imagery to evaluate three vegetation indices (NDVI, EVI, EVI2). We select EVI2 to parameterize an optical‐based ET algorithm and test the relationship between ET from Landsat and MODIS by regression approaches. Our analyses show significant decreases in VIs and ET for both the 20‐year and post‐pulse 5‐year periods. Over the last 20 years, EVI Landsat declined 34% (30% by EVIMODIS ) and ETLandsat‐EVI declined 38% (27% by ETMODIS‐EVI ), overall ca. 1.61 mm/day or 476 mm/year drop in ET; using PAM ETLandsat‐EVI the drop was from 1130 to 654 mm/year. Over the 5 years since the 2014 pulse flow, EVILandsat declined 20% (13% by EVIMODIS ) and ETLandsat‐EVI declined 23% (4% by ETMODIS‐EVI ) with a 0.77 mm/day or a 209 mm/year 5‐year drop in ET; using PAM ETLandsat‐EVI the drop was from 863 to 654 mm/year. Data and change maps show the pulse flow contributed enough water to slow the rate of loss, but only for the very short‐term (1–2 years). These findings are critically important as they suggest further deterioration of biodiversity, wildlife habitat and key ecosystem services due to anthropogenic diversions of water in the U.S. and Mexico and from land clearing, fires and plant‐related drought which affect hydrological processes. Abstract : Riparian reaches in the delta of the Colorado River have undergone reductions in green vegetation from human‐induced activities that have caused water stress to plants. The reduction is due to the diversion of surface water at the international border, groundwater losses, land clearing, fire and minimally from precipitation patterns. A key finding is that active restoration of native plants and timing of water deliveries has been beneficial in slowing the decrease over time in the two metrics in our study, vegetation greenness and plant water use, to nearly half. However, the success of the Minute 319 environmental pulse flow in 2014 was short‐lived (1–2 years) and then declines resumed. We measured declines over the last 20 years. Greenness as measured by vegetation indices (VIs) declined 34% (EVILandsat ) and 30% (EVIMODIS ), while ET losses were 1.58 mm/day (38%; ETLandsat‐EVI ) and 1.13 mm/day (27%;ETMODIS‐EVI ). A key finding is that in a few reaches, greenness declined as much as 44% with a corresponding ET loss of 624 mm/year or 2.13 mm/day (51%). We found that the full‐year PAM ETLandsat‐EVI dropped from 1, 130 mm/year in 2000 to 654 mm/year in 2019, a difference of 476 mm/year over 20 years. However, since the environmental pulse flow in 2014, declines in vegetation greenness over these past 5 years were less. Over the last 5 years, the VI signal decline was 20% (EVILandsat ) and 13% (EVIMODIS ), while ET losses were 0.77 mm/day (23%; ETLandsat‐EVI ) and 0.13 mm/day (4%; ETMODIS‐EVI ), a 5‐year drop of 209 mm/year. A key finding is that the pulse flow water in 2014 resulted in a 5‐year increase of 14–17% and ET of 0.81–1.00 mm/day, a difference of 267 mm/year, compared to the 20‐year data.